Personal Justice Beliefs, Perceived Discrimination, and Carotid Intima-media Thickness in Sexual Minority Young Adults. (September 2021) - Maschino, Leah; Cook, Stephanie; Lucas, Todd
Abstract : Background: Cardiovascular disease (CVD) disproportionately affects sexual minority men and is linked to discrimination-related stress. Belief in a just world is a coping strategy that can reduce stress and protect against CVD. However, these effects are unknown for sexual minorities. Here, we examine links between personal justice beliefs, discrimination, and Carotid Intima Media Thickness (CIMT) – a measure of atherosclerosis that can indicate subclinical CVD. Methods: Sexual minority male young adults (N = 69) completed measures of personal justice beliefs and everyday discrimination. CIMT imaging was used to compute common carotid artery intima-media thickness (CCA). Results: Multiple regressions revealed associations between justice beliefs, perceived discrimination, and CIMT that were moderated by age. Personal justice beliefs predicted less discrimination, especially among older males. Personal justice beliefs were also linked to greater CCA among older males. Conclusion: Believing in justice may embody a double-edged sword for minority CVD. Among sexual minority young men, belief in personal justice may reduce perceived discrimination, but may be deleteriously associated with biological processes that underlie CVD.